Cardiac secreted HSP90α exacerbates pressure overload myocardial hypertrophy and heart failure - Le Pan; Chenxing Huang; Xuejuan Jin; Jian Wu; Kejia Jin; Jingyi Lin; Ying Wang; Jianxuan Li; Chao Yin; Xiang Wang; Lei Zhang; Guoping Zhang; et al. (Redox Biology)
Sustained myocardial hypertrophy or left ventricular hypertrophy (LVH) triggered by pressure overload is strongly linked to adverse cardiovascular outcomes. Here, we investigated the clinical relationship between serum HSP90α (an isoform of HSP90) levels and LVH in patients with hypertension or aortic stenosis (AS) and explored underlying mechanisms in pressure overload mouse model. We built a pressure overload mouse model via transverse aortic constriction (TAC). Compared to controls, elevated serum HSP90α levels were observed in patients with hypertension or AS, and the levels positively correlated with LVH. Similarly, HSP90α levels increased in heart tissues from patients with obstructive hypertrophic cardiomyopathy (HCM), and in mice post-TAC. TAC induced the enhanced cardiac expression and secretion of HSP90α from cardiomyocytes and cardiac fibroblasts. Knockdown of HSP90α or blockade of extracellular HSP90α (eHSP90α) attenuated cardiac hypertrophy and dysfunction by inhibition of β-catenin/TCF7 signaling under pressure overload. Further analysis revealed that eHSP90α interacted with EC1-EC2 region of N-cadherin to activate β-catenin, enhancing the transcription of hypertrophic genes by TCF7, resulting in cardiac hypertrophy and dysfunction under pressure overload. These insights suggest the therapeutic potential of targeting HSP90α-initiated signaling pathway against cardiac hypertrophy and heart failure under pressure overload.